Practical electronics handbook - Sinclair, Ian Robertson (Newnes Butterworth-Heinemann, 1994)
This is the best value handbook on electronics you can buy. With new chapters and sections covering topics such as sensing components, connectors, soldering and unsoldering, this fourth edition contains all of the everyday information that anyone working in electronics will need. It provides a practical and comprehensive collection of circuits, rules of thumb and design data for professional engineers, students and enthusiasts, and therefore enough background to allow the understanding and development of a range of basic circuits.